Rapid preparation method of hollow fluorescent sphere glass structure and mold thereof
By adopting a fast preparation method of hollow fluorescent sphere glass structure, using double-layer mold pressing and Joule thermal ultra-fast high-temperature sintering technology, the problems of low light extraction efficiency, poor heat dissipation ability and long sintering time are solved, and efficient and low-cost fluorescent glass synthesis is achieved.
Patent Information
- Application Number
- CN202411920475.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-05-02
AI Technical Summary
The light extraction efficiency of existing fluorescent glasses is not high, the heat dissipation ability is poor, the sintering time is long and the cost is expensive, which affects the stability and life of the equipment.
The rapid preparation method of hollow fluorescent sphere glass structure is adopted, and the mixture of phosphor and glass powder is pressed through a double-layer mold to form hollow spherical glass with an inner surface microstructure, and sintered using Joule thermal ultra-fast high-temperature sintering process.
It greatly improves manufacturing efficiency, heat dissipation efficiency and light extraction efficiency, saves manufacturing costs, and realizes ultra-fast and low-cost synthesis of hollow fluorescent sphere glass, with excellent structural performance.
Smart Images

Figure CN119912141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorescent glass, and in particular to a rapid preparation method of a hollow fluorescent spherical glass structure and a mold thereof. Background Art
[0002] At present, laser-driven lighting based on laser diodes has attracted widespread attention in the field of solid-state lighting due to its high electro-optical efficiency and high power density. Fluorescent conversion materials are the core components that determine the energy efficiency of laser lighting and the color quality of display products. The traditional packaging mode of phosphor plus organic silicone has low thermal conductivity, and there are problems such as ablation, blackening, and failure under LD excitation. Among the emerging inorganic fluorescent materials, fluorescent glass has attracted widespread attention due to its advantages in production cost, preparation process, and flexible structural design.
[0003] Currently, the commonly used fluorescent glass is mostly in the shape of a thin film. Its two-dimensional structure limits the light extraction efficiency, making the illumination uneven and the luminous area limited. In addition, the laser heat is unevenly dispersed and the heat dissipation performance is limited. Under high-power density laser excitation, it shows a more obvious luminescence quenching phenomenon, which affects the stability and life of the equipment.
[0004] In the sintering process of fluorescent glass, the traditional solid-state sintering commonly used in industry requires long-term heat treatment of materials; spark plasma sintering requires high mechanical pressure and high pulse direct current, which is expensive at the expense of time; and microwave sintering has strict requirements on materials, and only materials with microwave absorption can be processed and sintered; In summary, the current structure of fluorescent glass and its preparation method have more or less problems such as low light extraction efficiency, poor heat dissipation capacity, long sintering time, and high cost; therefore, it is necessary to improve the structure of fluorescent glass and provide a simple and fast fluorescent glass manufacturing process to ensure the light efficiency, brightness and color quality of the device and reduce the production time. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the above-mentioned prior art and provide a method for quickly preparing a hollow fluorescent spherical glass structure and a mold thereof. The present invention produces a hollow spherical fluorescent glass with an inner surface microstructure under the premise of ensuring optical properties such as luminous flux, luminous efficiency and correlated color temperature under high-power laser irradiation, greatly improving manufacturing efficiency, heat dissipation efficiency and light extraction efficiency, and saving manufacturing costs.
[0006] The present invention is achieved through the following technical solutions: A mold for pressing a hollow fluorescent spherical glass structure, comprising an outer mold and an inner mold therein; The outer mold is a spherical structure; the spherical structure is formed by closing two hemispherical shells in a hemispherical shape; The inner mold is an expandable hollow sphere, which extends into the outer mold from the opening at the top; There is a gap between the inner mold and the outer mold, and the gap constitutes a mold cavity of the mold; The top of the inner mold is provided with a gas interface for introducing gas.
[0007] The outer surface of the inner mold is covered with micro protrusions.
[0008] The rapid preparation method of the hollow fluorescent spherical glass structure by pressing the above mold comprises the following steps: Step S1, adding phosphor and glass powder into a beaker and stirring to obtain a mixture; Step S2, laying the mixture along the inner surface shapes of the two hemispherical shells to a desired thickness, and continuously compacting the mixture to obtain two hemispherical shell structures of the mixture attached to the inner surfaces of the hemispherical shells; Step S3, closing the two hemispherical shells of the outer mold, and then extending the inner mold into the outer mold from the opening at the top of the outer mold, and filling the mixture into the mold cavity again to supplement the remaining gap in the mold cavity; introducing helium from the gas interface of the inner mold to make the inner mold with micro-protrusions on the outer surface expand gradually, and continuously pressurizing to the required pressure and then maintaining the pressure for 50-120s, adding ionized water from the opening at the top of the outer mold to wet the pressed mixture, and continue to maintain the pressure for 10-60s to obtain the compact structure of the hollow fluorescent sphere; Step S4, placing the processed hollow fluorescent sphere compact structure in a carbon heating body, heating the carbon heating body using Joule heating effect, adjusting the input current to control the heating rate and temperature of the device, and collecting the solidified semi-finished hollow fluorescent sphere after sintering; Step S5, surface treatment is performed on the semi-finished hollow fluorescent sphere that is solidified and formed by sintering in step S4, so as to finally obtain a hollow fluorescent sphere glass body.
[0009] In step S1, the phosphor powder and the glass powder are mixed in a mass ratio of 1:1.
[0010] The phosphor is YAG, YAGG, GdYAG or LSN.
[0011] The fluorescent powder and the glass powder are mixed in a mass ratio of 1:1 and stirred in a vacuum environment for 10-15 minutes.
[0012] The material of the outer mold is tungsten steel, stainless steel or aluminum-nickel alloy; the material of the inner mold is rubber.
[0013] The micro-protrusions are in the shape of a hemisphere, a cone or a polygon.
[0014] In step S4, when the hollow fluorescent sphere compacted structure 4 is placed in a carbon heating body for heating, it should be carried out in an environment filled with inert gas.
[0015] The inert gas is argon, helium or nitrogen.
[0016] Compared with the prior art, the present invention has the following advantages and effects: The present invention obtains a compact structure of a hollow fluorescent sphere with a specific surface microstructure by mixing glass powder and fluorescent powder in a mass ratio of 1:1, stirring the mixture in a vacuum environment, adding the mixture into a double-layer mold consisting of an inner and outer mold for pressing, and then placing the structure in an inert gas environment, sintering it using a Joule heat ultrafast high-temperature sintering device composed of graphite felt, and obtaining a semi-finished hollow fluorescent sphere that is solidified by adjusting current parameters, and finally performing surface treatment and testing to obtain a finished hollow fluorescent sphere.
[0017] The present invention changes the fluorescent glass from a two-dimensional thin film structure to a three-dimensional structure of a hollow fluorescent sphere. Its luminous area is larger than that of thin film fluorescent glass of the same volume, and the laser heat dissipation area is also increased. Microstructures are made on the inner surface of the hollow fluorescent sphere, which can make the light efficiently reflected inside, thereby improving the light extraction efficiency and providing more uniform light distribution.
[0018] The present invention adopts Joule heat ultrafast high temperature sintering process to prepare fluorescent glass, which can reach the sintering temperature in 5-10 seconds and complete sintering in 10-20 seconds, which can greatly improve the sintering rate and reduce the sintering time; The present invention only requires sintering in an inert gas environment, which greatly saves sintering costs; the present invention realizes ultra-fast and low-cost synthesis of hollow fluorescent spherical glass. Compared with the fluorescent glass commonly used in the existing industry, the process flow is simple, the cost is low, the operation is easy, and the structural performance is excellent, which opens up a new way for the rapid preparation of fluorescent glass suitable for laser-driven lighting. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a manufacturing process flow chart of the hollow fluorescent spherical glass structure of the present invention; Figure 2 is a schematic diagram of the process flow of step S1 in an embodiment of the present invention; Figure 3 Schematic diagram of a mold for pressing a hollow fluorescent spherical glass structure according to an embodiment of the present invention; Figure 4 is a schematic diagram of the process flow of steps S2 and S3 in an embodiment of the present invention; Figure 5 is a schematic diagram of the process flow of step S4 in an embodiment of the present invention; Figure 6is a schematic diagram of the process flow of step S5 in an embodiment of the present invention; Reference numerals in the figure: glove box 1; phosphor 11; glass powder 12; beaker 13; Mold 2; outer mold 210, inner mold 220; opening 211; hinge 212; micro protrusion 221; mixture hemispherical shell structure 3; hollow fluorescent sphere compact structure 4; current output module 51; temperature control module 52; Joule heating module 53; power connection module 54; semi-finished hollow fluorescent sphere 55; conductive copper sheet 541; alligator clip power cord 542; hollow fluorescent sphere glass body 6. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below in conjunction with specific embodiments.
[0021] like Figure 2 As shown, the YAG phosphor 11 and the glass powder 12 are mixed in the beaker 13 at a mass ratio of 1:1, the glove box 1 is evacuated to a vacuum, and the beaker 13 containing the mixture is stirred in the glove box 1 for 15 minutes.
[0022] Specifically, the YAG phosphor 11 can be replaced by fluorescent materials such as YAGG, GdYAG and LSN.
[0023] In this embodiment, if Figure 3 As shown, the mold 2 used in the pressing process is composed of an outer mold 210 and an inner mold 220. The outer mold 210 is composed of two hemispherical molds with hemispherical mold cavities, which are connected from the bottom by the hinge 212 and have an opening 211 on the top. The inner mold 220 enters the outer mold from the opening 211, and the surface of the inner mold 220 has micro-protrusions 221 (hemispherical microstructures).
[0024] The micro-protrusions 221 may be replaced by surface micro-structures such as cones and polygons.
[0025] The outer mold 210 is made of tungsten steel, has a thermal conductivity greater than 20 W·m-1K-1, is easy to process, is resistant to high temperatures, and is not prone to adhesion to glass.
[0026] The inner mold 220 is made of rubber and is inflated by injecting an inert gas to compress the mixture.
[0027] like Figure 4As shown, the stirred mixture is added to the outer mold 210, and then the raw material powder is cold isostatically pressed for 60 seconds at a pressure of 20 MPa to obtain two fluorescent glass hemispherical shell compact structures 3, and then the two hemispherical molds of the outer mold 210 are merged, and the inner mold 220 and a small amount of the mixture are put into the opening 211 at the upper part of the outer mold, and helium is introduced into the inner mold 220 to expand it, and deionized water is added after the mixture is continuously pressed for 120 seconds, and the pressure is continued to be maintained for 60 seconds to obtain the hollow fluorescent sphere compact structure 4; The mold cavities of the two hemispherical molds of the outer mold 210 are both composed of hemispherical surfaces with a radius of 12 mm.
[0028] By using the micro-protrusions 221 of different shapes, the hollow fluorescent sphere compacted structure 4 with different inner surfaces can be obtained, and the light transmittance and extraction rate will also change.
[0029] In this embodiment, if Figure 5 As shown, the Joule heat high-temperature rapid sintering device includes the current output module 51, the temperature control module 51, the Joule heating module 53, and the power connection module 54; the material of the Joule heating module 53 is a long cylindrical graphite felt with a length of 10 cm and a radius of 2 cm, which is located in the glove box 1, and helium is used as a protective gas to create an inert atmosphere; the power connection module includes the conductive copper sheet 541 and an alligator clip power cord 542, the conductive copper sheet 541 clamps and fixes both ends of the Joule heating module 53, and conductive silver paste is coated at the connection, and the alligator clip power cord 542 connects the other end of the conductive copper sheet to conduct current to heat the Joule heating module 53.
[0030] In this embodiment, the compacted hollow fluorescent sphere structure 4 is placed in the Joule heating module 53 and placed in the glove box 1 filled with helium. The alligator clip power cord 542 is passed through the glove box 1 to connect to the current output module 51 to output direct current. During the sintering process, the temperature control module 51 is started, and the spectral temperature measurement method is used to detect the sintering temperature of the compacted structure to adjust the power supply parameters. The heating current is controlled at 25A, the sintering time is 10-20s, and the sintering temperature reaches 1939 K, and the semi-finished hollow fluorescent sphere 55 is obtained.
[0031] The helium used to create an inert atmosphere can be replaced by argon, nitrogen, etc.
[0032] The spectral temperature measurement method adopted by the temperature control module 51 can be replaced by infrared temperature measurement, laser temperature measurement and other methods.
[0033] In this embodiment, if Figure 6As shown, the semi-finished hollow fluorescent sphere 55 obtained by sintering is subjected to surface treatments such as grinding and polishing to obtain the hollow fluorescent sphere glass body 6.
[0034] As described above, the present invention can be better implemented.
[0035] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A mold for pressing a hollow fluorescent spherical glass structure, characterized in that Including the outer mold and the inner mold therein; The outer mold is a spherical structure; the spherical structure is formed by closing two hemispherical shells in a hemispherical shape; The inner mold is an expandable hollow sphere, which extends into the outer mold from the opening at the top; There is a gap between the inner mold and the outer mold, and the gap constitutes a mold cavity of the mold; The top of the inner mold is provided with a gas interface for introducing gas.
2. The mold for pressing a hollow fluorescent spherical glass structure according to claim 1, characterized in that: The outer surface of the inner mold is covered with micro protrusions.
3. A rapid preparation method of a mold-pressed hollow fluorescent spherical glass structure according to claim 1 or 2, characterized in that: The following steps are involved: Step S1, adding phosphor and glass powder into a beaker and stirring to obtain a mixture; Step S2, laying the mixture along the inner surface shapes of the two hemispherical shells to a desired thickness, and continuously compacting the mixture to obtain two hemispherical shell structures of the mixture attached to the inner surfaces of the hemispherical shells; Step S3, closing the two hemispherical shells of the outer mold, and then extending the inner mold into the outer mold from the opening at the top of the outer mold, and filling the mixture into the mold cavity again to supplement the remaining gap in the mold cavity; introducing helium from the gas interface of the inner mold to make the inner mold with micro-protrusions on the outer surface expand gradually, and continuously pressurizing to the required pressure and then maintaining the pressure for 50-120s, adding ionized water from the opening at the top of the outer mold to wet the pressed mixture, and continue to maintain the pressure for 10-60s to obtain the compact structure of the hollow fluorescent sphere; Step S4, placing the processed hollow fluorescent sphere compact structure in a carbon heating body, heating the carbon heating body using Joule heating effect, adjusting the input current to control the heating rate and temperature of the device, and collecting the solidified semi-finished hollow fluorescent sphere after sintering; Step S5, surface treatment is performed on the semi-finished hollow fluorescent sphere that is solidified and formed by sintering in step S4, so as to finally obtain a hollow fluorescent sphere glass body.
4. The rapid preparation method of the mold-pressed hollow fluorescent sphere glass structure according to claim 3, characterized in that: In step S1, the phosphor powder and the glass powder are mixed in a mass ratio of 1:
1.
5. The rapid preparation method of the mold-pressed hollow fluorescent sphere glass structure according to claim 4, characterized in that: The phosphor is YAG, YAGG, GdYAG or LSN.
6. The rapid preparation method of the mold-pressed hollow fluorescent spherical glass structure according to claim 3, characterized in that: The material of the outer mold is tungsten steel, stainless steel or aluminum-nickel alloy; the material of the inner mold is rubber.
7. The rapid preparation method of the mold-pressed hollow fluorescent spherical glass structure according to claim 3, characterized in that: The micro-protrusions are in the shape of a hemisphere, a cone or a polygon.
8. The rapid preparation method of the mold-pressed hollow fluorescent spherical glass structure according to claim 3, characterized in that: In step S4, when the hollow fluorescent sphere compacted structure 4 is placed in a carbon heating body for heating, it should be carried out in an environment filled with inert gas.
9. The rapid preparation method of the mold-pressed hollow fluorescent spherical glass structure according to claim 8, characterized in that: The inert gas is argon, helium or nitrogen.
10. The rapid preparation method of the mold-pressed hollow fluorescent spherical glass structure according to claim 4, characterized in that: The phosphor powder and the glass powder are mixed in a mass ratio of 1:1 and stirred in a vacuum environment for 10-15 minutes.